Dynamic Adaptive Response of Pseudomonas aeruginosa to Clindamycin/Rifampicin-Impregnated Catheters - Kidon Sung; Jungwhan Chon; Ohgew Kweon; Seongwon Nho; Seongjae Kim; Miseon Park; Angel Paredes; Jin-Hee Lim; Saeed A. Khan; Kenneth Scott Phillips; Carl E. Cerniglia (Antibiotics, 2021)
Pseudomonas aeruginosa is the most common Gram-negative pathogen causing nosocomial multidrug resistant infections. It is a good biofilm producer and has the potential for contaminating medical devices. Despite the widespread use of antibacterial-impregnated catheters, little is known about the impacts of antibacterial coating on the pathogenesis of P. aeruginosa. In this study, we investigated the adaptive resistance potential of P. aeruginosa strain PAO1 in response to continuous antibiotic exposure from clindamycin/rifampicin-impregnated catheters (CR-IC). During exposure for 144 h to clindamycin and rifampicin released from CR-IC, strain PAO1 formed biofilms featuring elongated and swollen cells. There were 545 and 372 differentially expressed proteins (DEPs) identified in the planktonic and biofilm cells, respectively, by ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). Both Cluster of Orthologous Groups (COG) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses showed that the planktonic cells responded to the released antibiotics more actively than the biofilm cells, with metabolism and ribosomal biosynthesis-associated proteins being significantly over-expressed. Exposure to CR-IC increased the invasion capability of P. aeruginosa for Hela cells and upregulated the expression of certain groups of virulence proteins in both planktonic and biofilm cells, including the outer membrane associated (flagella, type IV pili and type III secretion system) and extracellular (pyoverdine) virulence proteins. Continuous exposure of P. aeruginosa to CR-IC also induced the overexpression of antibiotic resistance proteins, including porins, efflux pumps, translation and transcription proteins. However, these upregulations did not change phenotypic minimum inhibitory concentration (MIC) during the experimental timeframe. The concerning association between CR-IC and overexpression of virulence factors in P. aeruginosa suggests the need for additional investigation to determine if it results in adverse clinical outcomes.